Nothing personal, just business : a guided journey into organizational darkness - Stein, Howard F. (Quorum Books, 2001)
Through vignettes and case studies, this work demonstrates how brutal business practices have become. It shows the importance of psychodynamic mechanisms (especially counter-transference) in understanding and healing dysfunctional business, medical, and educational organizations.